PENGARUH MODEL PEMBELAJARAN PPSI (PROSEDUR PENGEMBANGAN SISTEM INSTRUKSIONAL) TERHADAP HASIL BELAJAR SEJARAH - Putut Wisnu Kurniawan (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The problem in this research is the low of students’ learning outcomes of history. It is caused by the students’ initiative in teaching and learning process. The purpose of this study was to determine the learning model ITS (Instructional Systems Development Procedure) learning model towards students’ learning outcomes of history at tenth grade of SMA PERSADA Bandar Lampung in academic year 2014/2015. The population in this research was 110 students and the sample was 27 students. In getting the sample, the writer used a cluster random sampling. The data in this research were collected by using experimental methods and testing technique as the main method, as well as technical documentation and study of literature as the supporting method. In analyzing the data, the writer used t-test formula.Based on the analysis of data, it is obtained t_hit = 5.24, while for the significant level of 5% t-daf = 2.00. The average score of the students who learn history through ITS (Instructional Systems Development Procedure) learning model is 83. While the average score of students who learn history through conventional technique is 73. It can be concluded that, there is influence of learning model using ITS (Instructional Systems Development Procedure) towards students’ learning outcomes of history at tenth grade of SMA PERSADA Bandar Lampung in academic year 2014/2015.